ANALISIS EFEKTIVITAS SISTEM INFORMASI AKUNTANSI SIKLUS PENDAPATAN PADA PT.GTS - Mega Anisha, - (2019)
This research aims to know the effectiveness of accounting information systems revenue cycle in PT. GTS engaged in the service of ' umrah and Hajj with an associate on the principal elements of the accounting information system. The methods used in this research is qualitative method with paradigm intepretif and etnometodologi approach. The research results showed that the system accounting information cycle revenue PT. GTS has been running effectively because it is already in compliance with the principal elements of the accounting information system. But the need for separation of functions in revenue cycle between the marketing function with receipt cash function of companies to prevent fraud carried out by related parts.